Human Endothelial Cells Maintain Anti-Aggregatory Activity for Platelets during Apoptosis - Xu, Wei; Favaloro, Emmanuel J.; Medbury, Heather; Zoellner, Hans (Thrombosis and Haemostasis, 2001)
Despite evidence of elevated levels of tissue factor and platelet binding by apoptotic endothelial cells, microthrombi do not appear to be associated with apoptotic endothelium and this suggests maintained anti-aggregatory activity for platelets. We report that anti-aggregatory activity is maintained by apoptotic endothelium obtained by serum and or matrix deprivation, which we propose as models for apoptotic endothelial cells released during microvascular remodelling and traumatic detachment respectively. Both apoptotic and non-apoptotic endothelium had strong anti-aggregatory activity for platelets stimulated with either ADP or thrombin. Inhibition experiments using L-NAME and indo-methacin indicated a role for nitric oxide and prostacyclin in this activity. Experiments with latex beads further confirmed that inhibited platelet aggregation by endothelium was not merely a non-specific phenomenon. These data support the idea that EC maintain active anti-thrombotic activity during apoptosis, consistent with maintained urokinase levels and canalicular fragmentation reported elsewhere.
Keywords: Endothelium; apoptosis; platelets; aggregation